PERTUMBUHAN DAN HASIL KEDELAI EDAMAME (Glycine max (L.) Merr.) DENGAN APLIKASI PUPUK ORGANIK GUANO DI TANAH TUKUNGAN - Riza Adrianoor Saputra; Jumar Jumar; Muhammad Hayatullah (Universitas Lambung Mangkurat, 2021)
Soybean is the third most consumed staple food after rice and corn. The need for soybeans continues to increase accompanied by an increase in population and the need for raw materials for the food processing industry such as tofu, tempeh, soy sauce, soy milk, etc. One type of soy that is harvested fresh is edamame soybeans. The number of farmers who grow edamame soybeans in South Kalimantan is still relatively few. This has the potential to be developed. However, the problem is that soybean productivity in South Kalimantan is still low. This is due to the low level of soil fertility, such as tukungan soil. Tukungan soil is a mound of soil in the middle of rice fields that farmers have deliberately made so that they can plant plants that do not like excess water. The use of guano organic fertilizer in edamame soybean cultivation can be a solution in overcoming soil fertility problems in tukungan soil. The purpose of this study was to determine the best dosage of guano organic fertilizer for the growth and yield of edamame soybeans in tukungan soil. The research was carried out from November 2019 to February 2020, at the Greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Universitas Lambung Mangkurat, Banjarbaru. This study used one factor completely randomized design. The factors studied were the dosage of guano organic fertilizer (K) which consisted of five levels, namely: k0 = 0 ton/ha, k1 = 10 ton/ha, k2 = 20 ton/ha, k3 = 30 ton/ha and k4 = 40 ton/ha. The results showed that the dose of 30 ton/ha of guano organic fertilizer was the best dose in increasing plant weight and pod weight of edamame soybean, respectively 41.93% and 67.62% compared to the control treatment.